Development of Tourism Potential in the Lipetsk Oblast as a Factor in Shaping Cultural and Geographical Space - POLYAKOVA, Irina Yevgenievna; IVANOVA, Raisa Mihailovna; SKROBOTOVA, Olga Vladimirovna (Journal of Environmental Management and Tourism, 2017)
The article focuses on researching methods of tourism potential development and promotion in the Lipetsk Oblast, Russian Federation, as a factor in shaping the region’s cultural and geographical space. Interdependence between the geo-cultural space and the territory’s tourism potential has been identified. Adopting the right approach to assess a capacity potential and to model and update human and geographical images, i.e. cultural keynotes of the destination under investigation, allows for the development of domestic and inbound tourism in the area. Major emphasis has been placed on the main means of promoting tourism potential, namely, the formation of the image-centered tourism development strategy based on updating cultural and historical dominant ideas.